2008
DOI: 10.1677/joe-07-0541
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral cardiovascular actions of adrenomedullin 5, a novel member of the calcitonin gene-related peptide family, in mammals

Abstract: Adrenomedullin 5 (AM5) is a new member of the calcitonin gene-related peptide (CGRP) family identified in teleost fish. Although its presence was suggested in the genome database of mammals, molecular identity and biological function of AM5 have not been examined yet. In this study, we cloned a cDNA encoding AM5 in the pig and examined its cardiovascular and renal effects. Putative mature AM5 was localized in the middle of prohormone and had potential signals for intermolecular ring formation and C-terminal am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
(53 reference statements)
3
25
1
Order By: Relevance
“…Cui et al (2008) reported that microinjection of AM2 into the NTS elevates arterial pressure and heart rate in urethane-anesthetized rats. Furthermore, Takei et al (2008) reported that AM5 injected into the cerebral ventricle dose-dependently increased arterial pressure and heart rate in urethane-anesthetized rats. These results suggest that centrally administered AM5 is involved in the cardiovascular system in rats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Cui et al (2008) reported that microinjection of AM2 into the NTS elevates arterial pressure and heart rate in urethane-anesthetized rats. Furthermore, Takei et al (2008) reported that AM5 injected into the cerebral ventricle dose-dependently increased arterial pressure and heart rate in urethane-anesthetized rats. These results suggest that centrally administered AM5 is involved in the cardiovascular system in rats.…”
Section: Discussionmentioning
confidence: 97%
“…In pigs, the AM5 gene was expressed abundantly in the spleen and thymus, slightly in the adrenal and pituitary, and undetectable in the brain . However, it remains a possibility that AM5 may exist in some restricted regions of the pig brain because they examined only a small part of the pig brain, including the ventral hypothalamic area (including the SON, organum vasculosum laminae terminalis, and median eminence; Takei et al 2008). Further studies such as ISH and RT-PCR using different parts of the brain may reveal the existence of AM5 in the pig brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major effects of AM2 in mammals known to date are on cardiovascular and body fluid regulation, similar to AM. The recently identified AM5 also induces hypotension after peripheral injection and hypertension after intracerebroventricular administration in mammals, but the peripheral effects are less potent than AM (35).…”
mentioning
confidence: 99%
“…ADM-1 and -2 are widely conserved in all vertebrates. However, ADM-5 is conserved in fish, amphibians and reptiles but has been lost in birds and many mammals, for example, humans, chimpanzees, rats and mice 13 , due to the loss of functional constraints. ADM-1, -2 and -5 are all expressed as pre-proproteins and contain secretory signal peptides and internal processing sites.…”
mentioning
confidence: 99%